Corruption as Seen in Mark Twain’s Short Story The Man Who Corrupted Hadleyburg - Gerung, Grace; Wuntu, Ceisy N.; Rorimpandey, Rinny (Program Studi Pendidikan Bahasa Inggris, 2024)
This study aims at analysing the story's portrayal of corruption. This study is a qualitative research, and this study employed an objective approach of M.H Abrams in analysing the data of corruption as seen in